Классификация патентов на полезные модели Петрозаводского государственного университета - Kovaliok N. S. (Новое слово в науке: перспективы развития, 2016)
using the site of the Federal Institute of Industrial Property the classification of patents for utility models, patented Petrozavodsk State University in 2015.
Keywords: патенты; полезные модели; Петрозаводский университет; patents; Petrozavodsk State University; utility models